Pituitary hyperplasia secondary to primary hypothyroidism - Martinez Quintero, Beatriz (Clin Case Rep, 2020)
Severe primary hypothyroidism should be considered in the differential diagnosis of pituitary enlargement. Thyroid hormone replacement therapy should lead to regression of pituitary hyperplasia.